A New variant of the McEliece cryptosystem based on the Smith form of convolutional codes. Issue 3 (4th May 2018) - Moufek, Hamza; Guenda, Kenza
ABSTRACT: In this article, the authors propose a new version of the McEliece cryptosystem based on the Smith form of convolutional codes. They use the Smith form to hide a part of the code in the public matrix, and they leave the other part secret. The secret part will then be used for decryption. They hide this part by multiplying it on the left by a random matrix, and they add a random matrix which has a few conditions. Their scheme has a small public key size compared to the original McEliece scheme and resists the unique decoding attack against convolutional structure presented at the conference PQCrypto 2013 by Landais and Tillich. Further, the exhaustive search attack is infeasible on their system.